Peculiarities of professional tarining of higher education seekers of pedagogical specialties in conditions of emergency remote teaching (on the example of classical and technical universities) - IhnatiukОlha; KomyshanАnatolii; Bykova, Maryna (Scientific notes of the pedagogical department, 2020)
The article considers the problem of organization of professional training of higher education seekers of pedagogical profile in conditions of emergency remote teaching on the example of classical and technical universities. The authors clarified the essence of the terminological field of research «online education», «mobile learning», «emergency remote teaching», and characterized their features. Based on scientific generalizations and results of empirical research, essential features of organization of professional training of higher education seekers of pedagogical specialties in terms of classical and technical universities were determined, the algorithm of certain actions, which will lead to achieving success in educational activity, and its components were named. The necessity of establishing contact between all participants of educational process; the necessity of setting priorities in determining the workload of students with educational material; the necessity of implementing a competence building approach in the organization of individual work of students; the necessity of using cooperation technology; the necessity of choosing and implementing cloud tools of virtual interaction of participants of the educational process were characterized. In the course of questioning higher education seekers of pedagogical specialties in terms of classical and technical universities, the peculiarities of organization of professional training of future higher education teachers in conditions of emergency remote teaching, their influence on the success of higher education seekers in professional training and motivation to study were established.